A Performance Analysis Method of Gear Drive System Coupled with Elastic Supports - Dong Huimin; Liang Shiwen; Zhang Chuang (Jixie chuandong, 2018)
Introducing the combination of multi-dimension spring elements as the equivalent of elastic bearings and gearbox,an equivalent model of gear drive system coupled with elastic supports is proposed,with the coupling relationships between the shaft-bearing-gearbox supports and between the bearing holes of gearbox expressed as the displacement constraint equations of elastic supports. Combining with the FE contact analysis model of gear set,an analysis method of transmission performance is established. Taking a single-stage helical gear train as an instance,the influence of the supporting forms and rigidity on transmission performance indexes,including transmission error and the contact stress distribution on tooth surfaces,is analyzed by using this method. The analysis results indicate the method reflects the influence of supporting rigidity characteristics on transmission performance more veritably and comprehensively than empirical formulas. A guidance for the rigidity design of supports is provided.